MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MIND MAPPING PADA MATA PELAJARAN IPS KELAS VIII SMPN 56 SURABAYA - Safitri, Wiwik Wida; Purnomo, Nugroho Hari; Yudiana, Arin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the learning outcomes of grade VIII students of SMPN 56 Surabaya by applying a mind mapping learning design. This research is included in the collaborative classroom action research (PTKK). This is done during two cycles, where the cycle consists of planning, implementation, action, evaluation and reflection. The data obtained to conduct PTKK research is the learning outcomes of students taken from the results of the application using a learning method in the form of mind mapping. The results of this study have explained that with the results of learning improvement that has been carried out through the second cycle, it can be concluded that through the application of learning using mind mapping, it can provide changes in learning outcomes that increase in social studies subjects in grade VIII of SMPN 56 Surabaya. This is evidenced by the results of learning completeness that have been obtained by students in the first cycle stage, which is 47% while in the second cycle stage it is 86%.